Correction: Villalva et al. Antioxidant, Anti-Inflammatory, and Antibacterial Properties of an Achillea millefolium L. Extract and Its Fractions Obtained by Supercritical Anti-Solvent Fractionation against Helicobacter pylori. Antioxidants 2022, 11, 1849 - Marisol Villalva; Jose Manuel Silvan; Teresa Alarcón-Cavero; David Villanueva-Bermejo; Laura Jaime; Susana Santoyo; Adolfo J. Martinez-Rodriguez (Antioxidants, 2024)
Table S1 in the Supplementary Material (Phenolic compounds identified in yarrow samples by using HPLC-ESI-QTOF-MS) in the original paper [...]